P‐4: Electrical Characteristics of Dual‐Gate CAAC‐IGZO FET with Self‐Aligned Top Gate. Issue 1 (May 2016) - Honda, Ryunosuke; Suzuki, Akio; Matsuda, Shinpei; Saito, Satoru; Shima, Yukinori; Koezuka, Junichi; Yamazaki, Shunpei
Abstract : We fabricated dual‐gate CAAC‐IGZO FETs with self‐aligned top gates and investigated their electrical characteristics. The drain current was larger than expectedfrom the GI capacitance ratio to single‐gate FETs. Device simulation results suggest that shallow trap states and increase in electron mobility by self‐heating of FETs can explain the large drain current.